Ultrasonographic Diagnosis of Twin-to-Twin Transfusion Syndrome - Reyna-Villasmil, Eduardo; Briceño-Pérez, Carlos; Briceño-Sanabria, Juan C. (American Journal of Perinatology, 2022)
Introduction Twin-twin transfusion syndrome (TTTS) is a typical complication of monochorionic twin pregnancies (MCTP). Placental vessels that communicate in the chorionic plate between donor and recipient, are responsible for the imbalance of blood flow. Circulatory imbalance causes hypovolemia in donor and hypervolemia in recipient fetus. In a typical case, recipient fetus develops polyhydramnios, weight gain, cardiomegaly and hydrops fetalis. In contrast, donor fetus develops oligohydramnios and fetal growth restriction.Aim The objective of this review is to evaluate in detail the main diagnostic aspects and add other important data for diagnosis of TTTS.Scientific bases The main diagnostic event for this condition is based on the ultrasonographic discovery of oligohydramnios-polyhydramnios sequence. Other useful elements for diagnosis, staging and prognosis are fetal urinary bladder visualization, urinary bladder volumen measurements, edema of subcutaneous and/or generalized tissue edema, Doppler flow velocity waves and cardiac evaluation.Conclusion Considerations regarding diagnosis of TTTS make it possible to emphasize that role of physicians treating patients with MCTP is to identify ultrasound sequence of oligohydramnios-polyhydramnios. Other ultrasonographic fetal data as fetal urinary bladder visualization, urinary bladder volumen measurements, edema of subcutaneous and/or generalized tissue edema, Doppler flow velocity waves and cardiac evaluation; may help diagnosis, staging and prognosis of TTTS. It is their responsibility to accurately assess severity, therapeutic possibilities and prognosis.Key Points
Keywords: twin-twin transfusion syndrome; twin pregnancy; prenatal diagnosis; ultrasound; complications